2015
DOI: 10.4238/2015.march.13.8
|View full text |Cite
|
Sign up to set email alerts
|

EGFR gene polymorphisms -216G>T and -191C>A are risk markers for gastric cancer in Mexican population

Abstract: ABSTRACT. Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein with tyrosine-kinase activity that plays an important role in multiple cellular functions. EGFR overexpression has been observed in several types of tumors and it is significantly associated with disease stage, survival, prognosis, and progression of cancer. The polymorphisms -216G>T, -191C>A, and (CA) n first intervening sequence 1803 EGFR polymorphisms and gastric cancer risk ©FUNPEC-RP www.funpecrp.com.br Genetics and Molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“… 40 Moreover, MAPK1 (c.857–3854A > C and c.119 + 21641G > A), RAF1 (c.1669-36C > T) and HRAS (c.-1115T > C) intronic variants increased GA susceptibility on the Chilean population, 45 even when they were initially reported as variables of uncertain significance in ClinVar. Similar disparities between studies were found in Mexican population, where an increased GA susceptibility was associated with the EGFR promotor region variants c.-216G > T, c.-191C > A 49 (related to augmented expression of EGFR protein), the ERBB2 intronic variants c.-18 + 1614C > T, c.-18 + 3073G > T and the missense variant c.3418C > G, 50 classified as variables of uncertain significance in ClinVar. Also, a decreased susceptibility was associated with the TGF-β promoter variant c.-509C > T which is associated with higher TGF-β plasmatic concentration.…”
Section: Germline Risk Variants Associated To Sporadic Ga In Latamsupporting
confidence: 69%
“… 40 Moreover, MAPK1 (c.857–3854A > C and c.119 + 21641G > A), RAF1 (c.1669-36C > T) and HRAS (c.-1115T > C) intronic variants increased GA susceptibility on the Chilean population, 45 even when they were initially reported as variables of uncertain significance in ClinVar. Similar disparities between studies were found in Mexican population, where an increased GA susceptibility was associated with the EGFR promotor region variants c.-216G > T, c.-191C > A 49 (related to augmented expression of EGFR protein), the ERBB2 intronic variants c.-18 + 1614C > T, c.-18 + 3073G > T and the missense variant c.3418C > G, 50 classified as variables of uncertain significance in ClinVar. Also, a decreased susceptibility was associated with the TGF-β promoter variant c.-509C > T which is associated with higher TGF-β plasmatic concentration.…”
Section: Germline Risk Variants Associated To Sporadic Ga In Latamsupporting
confidence: 69%
“…Likewise, certain EGFR genetic variations have also been shown to change EGFR protein levels in the body, including lungs (Nie et al, 2015), and subsequently modulate cancer susceptibility. In accordance with this, the variations in EGFR gene have been shown to modulate risk of several types of cancers, including gastric (Torres-Jasso et al, 2015), bladder (Chu et al, 2013), breast (Sobti et al, 2012) and lung cancer (Bashir et al, 2018;Feng et al, 2014;X. Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 58%
“…Both -216G>T and 191 C>A were associated with the risk of developing gastric cancer [20]. -191C/A (rs712830) was also associated with lung cancer [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…AG/GG rs2237051 (non-synonymous exon region) and AG/GG rs3733625 (3' untranslated region) variants of EGF gene were identified as susceptibility factors in a study conducted on Chinese population [19]. A study based on Mexican population suggested the association of -216G>T, 191C>A polymorphisms of EGFR and the risk of developing gastric cancer [20].…”
Section: Epidermal Growth Factor (Egf) Signaling Pathway and Gastric Cancermentioning
confidence: 99%